Determinants of Juvenile Delinquency: A Global Systematic Review of Risk and Protective Factors Among Adolescents (2000–2024) - Putra Satria Sampurna; Niken Hartati; Mardianto (Da'wa Faculty of Islamic State University Salatiga, 2025)
Juvenile delinquency is a complex issue driven by interactions between individual, social, and structural factors. This systematic literature review uses the PRISMA 2020 guidelines to analyze empirical evidence on risk and protective factors for adolescent delinquency published between 2000 and 2024. From an initial search of 832 records in Scopus, we selected 15 peer-reviewed studies for narrative synthesis. The results indicate that delinquency stems from problems across multiple ecological levels. The most consistent risk factors identified were family dysfunction, specifically maltreatment, adverse childhood experiences (ACEs), and parental incarceration, and association with delinquent peers. Conversely, protective factors function as active buffers rather than just the absence of risk. Key elements that significantly reduce delinquency include positive parenting, secure parent–child attachment, school connectedness, self-regulation, empathy, and future academic aspirations. The review highlights early to mid-adolescence as a critical window for intervention and suggests that prevention strategies should focus on building resilience through family and school support.